MANAJEMEN SINERGIS PESANTREN-MADRASAH DI ERA MODERN SEBAGAI ALTERNATIF PENDIDIKAN ISLAM INDONESIA - Amin Maghfuri (POTENSIA: Jurnal Kependidikan Islam, 2020)
The existence of madrasa or school based in pesantren has been impressed as an institution that stands and has a spirit (ruh) that is different from the pesantren. Even if these two institutions can synergize positively, it is possible to produce better quality output. This research is intended to examine in depth the opportunities to synergize the Islamic education system between pesantren and madrasas in order to become more effective educational institutions. This research is qualitative research with emphasis on the study of literature. The results of this study indicate that the opportunity to synergize pesantren and madrasas as alternative educational institutions is very wide considering the education system that runs between the two is generally still separate. This step can be started by uniting management into an integral system, implementing an integral curriculum and evaluating comprehensively.